Altered Gene Expression in Prefrontal Cortex of a Fabry Disease Mouse Model - Kummer, Kai K.; Kalpachidou, Theodora; Mitrić, Miodrag; Langeslag, Michiel; Kress, Michaela (Frontiers in Molecular Neuroscience, 2018)
Fabry disease is an X-chromosome linked hereditary disease that is caused by loss of function mutations in the α-galactosidase A (α-Gal A) gene, resulting in defective glycolipid degradation and subsequent accumulation of globotriaosylceramide (Gb3) in different tissues, including vascular endothelial cells and neurons in the peripheral and central nervous system. We recently reported a differential gene expression profile of α-Gal A(-/0) mouse dorsal root ganglia, an established animal model of Fabry disease, thereby providing new gene targets that might underlie the neuropathic pain related symptoms. To investigate the cognitive symptoms experienced by Fabry patients, we performed one-color based hybridization microarray expression profiling of prefrontal cortex samples from adult α-Gal A(-/0) mice and age-matched wildtype controls, followed by protein-protein interaction and pathway analyses for the differentially regulated mRNAs. We found that from a total of 381 differentially expressed genes, 135 genes were significantly upregulated, whereas 246 genes were significantly downregulated between α-Gal A(-/0) mice and wildtype controls. Enrichment analysis for downregulated genes revealed mainly immune related pathways, including immune/defense responses, regulation of cytokine production, as well as signaling and transport regulation pathways. Further analysis of the regulated genes revealed a large number of genes involved in neurodegeneration. The current analysis for the first time presents a differential gene expression profile of central nervous system tissue from α-Gal A(-/0) mice, thereby providing novel knowledge on the deregulation and a possible contribution of gene expression to Fabry disease related brain pathologies.